Mineral Policies (punctum books, 2022)
Mineral Policies provides a record of an art residency organized by ZETA Center for Contemporary Art in the mining region of Bulqiza in northeastern Albania, where four artists and activists from Albania, Blerta Hoçia, Diana Malaj, Pleurad Xhafa, and Ergin Zaloshnja, created a collective body of works in close proximity with the local miners, while still maintaining their own discrete sphere of action. This residency followed by a public exhibition, Each Strike Leads to the Next, featuring video works produced during the residency as well as a series of object, curated by Vincent W.J. van Gerven Oei, director of the Department of Eagles in Tirana.